Temporal stress in the operating room: brain engagement promotes "coping" and disengagement prompts "choking" - Modi,HN; SIngh,H; Orihuela-Espina,F; Athanasiou,T; Fiorentino,F; Yang,GZ; Darzi,A; Leff,DR (Annals of Surgery, 2017)
Objective:To investigate the impact of time pressure (TP) on prefrontalactivation and technical performance in surgical residents during a laparo-scopic suturing task.Background:Neural mechanisms enabling surgeons to maintain perform-ance and cope with operative stressors are unclear. The prefrontal cortex(PFC) is implicated due to its role in attention, concentration, and perform-ance monitoring.Methods:A total of 33 residents [Postgraduate Year (PGY)1 – 2¼15,PGY3– 4¼8, and PGY5¼10] performed a laparoscopic suturing taskunder ‘‘self-paced’’ (SP) and ‘‘TP’’ conditions (TP¼maximum 2 minutes perknot). Subjective workload was quantified using the Surgical Task LoadIndex. PFC activation was inferred using optical neuroimaging. Technicalskill was assessed using progression scores (au), error scores (mm), leakvolumes (mL), and knot tensile strengths (N).Results:TP led to greater perceived workload amongst all residents (meanSurgical Task Load Index score SD: PGY1 – 2: SP¼160.3 24.8 vs TP¼202.1 45.4,P<0.001; PGY3 – 4: SP¼123.0 52.0 vs TP¼172.5 43.1,P<0.01; PGY5: SP¼105.8 55.3 vs TP¼159.1 63.1,P<0.05).Amongst PGY1– 2 and PGY3– 4, deterioration in task progression, errorscores and knot tensile strength (P<0.05), and diminished PFC activationwas observed under TP. In PGY5, TP resulted in inferior task progression anderror scores (P<0.05), but preservation of knot tensile strength. Furthermore,PGY5 exhibited less attenuation of PFC activation under TP, and greateractivation than either PGY1 – 2 or PGY3 – 4 under both experimental con-ditions (P<0.05).Conclusions:Senior residents cope better with temporal demands and exhibitgreater technical performance stability under pressure, possibly due to